Jacob Burckhardt and his Athens or How to Shape an Authoritarian Democratic State - Moerbeck, Guilherme (Classica - Revista Brasileira de Estudos Clássicos, 2018)
This article was organized in three parts. In the first one, a concise introduction to the History of Greek Culture and its historical environment is presented. The focus of the second part lies on Burckhardt’s ideas on the emergence of the polis in Ancient Greece, and how the main thoughts of the Swiss historian tend to materialize in the Ancient past some theoretical conceptions of the nineteenth century. The Athens of Burckhardt is analyzed in the final part of this paper; the core of the author’s approach, and the way he built the idea of the “state as evil” to the democratic Athens of the fifth and the sixth centuries BC are explained. At last, the very meaning of Burckhardt’s Athens – a city-state degenerated by the government of its demoralized mob rule –, is discussed.